Analysis of Occupational Safety of Boat Lift Net’s Fishermen at the Bungus Ocean Fishing Port (PPS) Bungus West Sumatra - Sari, Sukma Ranum; Isnaniah, Isnaniah; Nasution, Polaris; Toni, Yulian (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2024)
Boat lift nets are one of the fishing gears in PPS Bungus, data from December 2021; 142 Bagan boat boats departed to carry out fishing operations with the number of fishermen boats 6 - 21 people and the weight of the ship 8-30 GT. In recent years, there have been several work accidents experienced by Bagan boat fishermen, such as falling while walking on the boat deck, fatigue, stepping on rotten wood, and broken hands. This study aims to determine the cases of work accidents that occurred in boat-bagan fishermen in the period January 2022 - January 2023, describe the activities carried out by boat-bagan fishermen, and determine the level of risk experienced by boat-bagan fishermen. This study uses a descriptive observational method with data analysis of probability concepts, JSA, and HIRA using the 2004 Australia and New Zealand standard risk control matrix. The results showed that the activities carried out in the operation preparation stage at PPS Bungus were mainly carried out by laborers (non-fishermen), work accidents in 7 operation activities were classified into five low-risk accidents and two moderate-risk and work accidents in the post-operation stage occurred 4 out of 7 activities which were classified into three common risk accidents and one medium risk.